DA AVERSÃO À DESCOBERTA: atitudes em relação à Matemática na formação de futuros professores dos anos iniciais - CÍNTIA RAQUEL FERREIRA MERCADO DE ALMEIDA (2021)
This research is linked to the Postgraduate Program in Mathematics Education at the Federal University of Mato Grosso do Sul (UFMS), along the research line "Teacher Training and Curriculum". It aims to understand to what extent the practices developed in the Pedagogy graduation approach and/or distance the adult future teachers from Mathematics Education, as well as which attitudes these (students) develop during the discipline responsible for the approach of contents and methodologies linked to mathematical knowledge. To this end, the context of data production was developed, via participant observation, during a Teaching Internship in Higher Education in the subject "Foundations and Methodologies of Mathematics Teaching", in a 4th semester class of the Pedagogy undergraduate course in the Faculty of Education (FAED/UFMS). The theoretical contribution is based on the field of Psychology of Mathematics Education in an interlocution with the initial formation of teachers. The study is framed as a qualiquantitative research, of descriptive-analytical character, whose instruments adopted to produce the data with the students were questionnaires, written narratives and the "Attitude Scale" (AIKEN; DREGER, 1963), translated, adapted and validated by Brito (1996). The results point, firstly, to the challenge of the teacher trainer, which consists in "breaking" the initial barrier of "fears and anxieties" arising from negative attitudes towards mathematics, constituted by the students' experiences in Basic Education, which are recalled when they enter the University during the development of the subject. With the conclusion of the work, it is possible to make the inference that the practices and methodologies used by the teacher trainer, in the case researched, revealed indications of a change from a negative to a positive attitude and brought action indicators for new experiences such as, for example, contact with manipulative materials, trends in Mathematics Education, content and exploratory methodologies, which raise the need to think about different forms of theoretical, methodological and conceptual approach to Mathematics with the pedagogue in training. KEY WORDS: Psychology of Mathematics Education. Pedagogy. Attitudes.